Widows in India : study of Varanasi and Vrindavan - Pathak, Bindeshwar (Rawat Publications:, 2016)
This heart-wrenching book on widows in contemporary India delves into multiple forms of material and emotional deprivation including a most oppressive kind of renunciation forced on the widows living in Varanasi and Vrindavan. Seeing the things from the suffering women's perspective, it questions the exclusivity of their renunciatory life prescribed by the Hindu Dharmashastras. Among other things, this work argues powerfully that the widows need a measure of social security for their sheer material survival, as they have for long been subjected to humiliation, neglect and blatant exploitation. In spite of modern India's constitutional provisions which grant equal rights to women, a large section of these women continue to suffer due to the heterogeneous and hierarchical nature of our social structure based on most glaring forms of socio-economic inequalities. The plight of widows is very pathetic because of the longstanding hold of orthodoxy, obscurantism and superstitious beliefs. Besides cruel frustrations of widowhood, the widows suffer from severe social, economic and cultural deprivations. Concerned with social and economic conditions of widows and their dependent children, this empathetic study seeks to understand: What are the overwhelming problems of widows? Do the widows think that widowhood has affected their social life in a cruel way? How do the widows cope with the changing times and changing society? Besides providing insight into the socio-psychological aspects of widowhood, this study investigates the people's attitude towards the widows and their own self-image. The book also elucidates and suggests ways and means to be adopted by the state, civil society organizations and the people as a whole in order to change the mindset of the widows and reorient them to take life in their own hands instead of being passive beneficiaries of others' charities.